Analisis Faktor-Faktor Yang MempengaruhiPertumbuhan Ekonomi Kota Surakarta Tahun 1987-2014 - Respati, Yurinda Citra; , Eni Setyowati.,S.E.,M.Si (2017)
This study, entitled Analysis of Factors Affecting Economic Growth Surakarta Year 1987-2014. The purpose of this study to analyze the effect of regional income, population, inflation, and employment in the short term and long term to the gross domestic product Surakarta years 1987-2014. This study uses an analytical tool Error Correction Model (ECM). Based on the research results of short-term analysis of inflation has a negative and significant effect on the level of α = 0.05. While the influence of local revenue, population and labor force does not have a significant effect on the gross domestic product. The results of long-term analysis of local revenue and inflation have significant negative effect on gross domestic product at the level of α = 0.05. While the number of population and employment in the long term have no effect on gross domestrik product.